The new science of intimate relationships - Fletcher, Garth J. O.; Wiley InterScience (Online service) (Malden, Mass. : Blackwell, 2002)
In this elegantly written and provocative book, Garth Fletcher, one of the world's leading relationship scientists, provides an antidote to the avalanche of pop-psychology books on intimate relationships. Integrating the latest scientific work from social psychology and evolutionary psychology, with contributions from clinical psychology and anthropology, he analyses and answers questions such as: how do people know they are in good relationships? does good communication produce successful relationships? where does love come from? do men have stronger sex drives than women? why do people sometimes batter or kill their partners?The answers provided are never less than fascinating and are often surprising. Fletcher dissects the arguments surging around evolutionary and social psychological theories. He also authoritatively describes the reality of the intimate lives and minds of both men and women, exploding the stereotypes and myths of pop psychology as he goes. Fletcher has written a book that is rigorous, and true to the science, but is also accessible and engagingly written.
1. The new science of intimate relationships -- pt. 1. Three theoretical planks -- 2. The intimate relationship mind : theories about theories about theories -- 3. The origins of the intimate relationship mind -- 4. Love and other emotions in intimate relationships -- pt. 2. The development of intimate relationships -- 5. Reading minds and personalities in intimate relationships -- 6. Communication and relationship success -- 7. Attachment and intimacy -- 8. Selecting mates and relationships -- pt. 3. Sex and violence -- 9. Sex and passion -- 10. The strange case of aggression in intimate relationships -- pt. 4. Conclusion -- 11. Assembling the intimate relationship mind.
Includes bibliographical references (pages 291-315) and index.
Print version record.
Keywords: Intimacy (Psychology); Interpersonal relations; Intimité; Relations humaines; FAMILY & RELATIONSHIPS -- Interpersonal Relations; PSYCHOLOGY -- Interpersonal Relations; Interpersonal relations; Intimacy (Psychology); Intimiteit; Interpersoonlijke relaties; Electronic books